2014
DOI: 10.1371/journal.pone.0099934
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Mechanical and the Human Mind: Spontaneous Mimicry of a Physically Present Android

Abstract: The spontaneous mimicry of others' emotional facial expressions constitutes a rudimentary form of empathy and facilitates social understanding. Here, we show that human participants spontaneously match facial expressions of an android physically present in the room with them. This mimicry occurs even though these participants find the android unsettling and are fully aware that it lacks intentionality. Interestingly, a video of that same android elicits weaker mimicry reactions, occurring only in participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 39 publications
2
61
2
1
Order By: Relevance
“…The possibility that rapid facial reactions reflect competitive considerations is suggested by recent work on human reactions to android's emotional expressions of anger and joy. In the initial work, setting the stage for this, Hofree et al (2014) have shown that under "default condition"…”
Section: Modulation Of Spontaneous Mimicry By Social Contextmentioning
confidence: 99%
“…The possibility that rapid facial reactions reflect competitive considerations is suggested by recent work on human reactions to android's emotional expressions of anger and joy. In the initial work, setting the stage for this, Hofree et al (2014) have shown that under "default condition"…”
Section: Modulation Of Spontaneous Mimicry By Social Contextmentioning
confidence: 99%
“…To further understand the features controlling spontaneous mimicry, we examined spontaneous responses to expressions of anger and joy generated by a human and an android (Hofree et al 2014). The human and android expressions were very similar in appearance and temporal dynamics (for details see Wu et al 2009).…”
Section: Facial Emotionmentioning
confidence: 99%
“…In addition, people also recognize physically present robots’ emotions more accurately, and even report higher levels of empathy for robots with whom they share the same space . A recent study showed that the presence of an android robot directly influences perceived humanness and spontaneous mimicry by participants . First, participants rated the android higher on human‐likeness when it was collocated with them, compared to being presented on a computer screen.…”
Section: Impact Of Artificial Agent's Visual Featuresmentioning
confidence: 99%